Kampania 1814 roku we Francji w świetle „Gazety Krakowskiej” - Wojewódzki, Ireneusz (In Gremium. Studies in History, Culture and Politics, 2016)
The campaign of 1814 in France in the light of „Gazeta Krakowska” The campaign of 1814 in France was one of Napoleon’s finest feats as a commander, although today in Poland it is somewhat forgotten. In contrast, Napoleon’s contemporaries followed the campaign with great interest. For citizens of the Duchy of Warsaw a main source of information was the press. This article presents in details the reports of „Gazeta Krakowska” („Cracow Gazette”) which are a reflection of each stage of the campaign. The gazette gives a wide picture of the campaign, focusing mainly on military aspects, often surprises readers with precision of information and quotations. It is based, however, only on foreign sources, and the gazette is repeating the point of view dictated by the authorities from Vienna. Consequently, it is silent about participation of Poles in the struggles in France, which shows that it was under pressure of censorship. The image of the campaign showed by „Gazeta Krakowska” is distorted, however, it is soft distortion, and sometimes there is a different perspective.